Jewish religious life in the Persian period - Smith, Morton (The Cambridge history of Judaism ; Vol. 1: Introduction, the Persian period, 2004)
The ‘Persian period’ – roughly, the two centuries from Cyrus ‘capture of Babylon in 539 to Alexander’s capture of Tyre in 332 b.c.e. – presents us with such variety in what may loosely be called ‘Jewish religious life’ that it raises the question, what is meant by ‘Jewish’? The adjective derives from the noun ‘Jews’, Yehudim in Hebrew, Yehudin in Aramaic. For these terms there is on the one hand the territorial definition, ‘residents of Judea’, implied, for example, by the reference to the Persian ‘governor of Judea’ as ‘governor of the Jews’ (Ezra 6: 7, purportedly quoting a letter of Darius I); on the other hand, the ethnic ‘descendants of Judeans’, the members of the Persian garrison in Elephantine, settled there for well over a century, still called themselves Yehudin although they had intermarried with Egyptians and worshipped a number of deities besides Yahweh. A third definition is implied by the uses in Ezra 4: 12; 5: 4–5, which equate ‘the Jews’ with the exiles returned from Babylonia, excluding the population left in Palestine. These Jews worship only ‘the God of heaven and earth’ (that is, Yahweh), and explain their history in terms reminiscent of Deuteronomy (Ezra 5:11). Other documents suggest other definitions – for example, Nehemiah's apology (notably 5: 1, 17) refers to ‘the Jews’ as if they were a privileged class in Jerusalem. If more texts were preserved we should probably have yet more variety.